Optimizing Soft Selling-Based Promotional Strategies Through Facebook Content at Taska Cendekiawan Ceria, Penang - Hawa Rahmayani; Alfi Amalia (International Conference on Islamic Economic (ICIE), 2026)
This study aims to analyze the optimization of a soft-selling-based promotional strategy through Facebook content at Taska Cendekiawan Ceria, Penang. The study employed a qualitative descriptive approach, with data collected through Facebook content observation, interviews, and documentation. The informants consisted of the head of the childcare center, the teacher responsible for managing the Facebook account, and parents of enrolled children. Data were analyzed using the stages of data reduction, data display, and conclusion drawing, while data trustworthiness was ensured through source, method, and theory triangulation. The findings indicate that Facebook promotional activities are still dominated by informational posts and documentation of daily activities, resulting in the suboptimal implementation of the three soft selling dimensions, namely feeling, implicit message, and image. This condition contributes to low audience engagement and limits the development of emotional connections and parental trust in the institution. The study suggests that promotional strategies can be optimized by developing storytelling-based content, delivering promotional messages implicitly, maintaining a consistent visual identity, and conducting regular engagement evaluations. This research proposes a soft-selling-based promotional strategy model that can enhance the effectiveness of Facebook promotion while strengthening the institutional image of Taska Cendekiawan Ceria as an early childhood education institution.